Evaluation of porB PCR-Amplicon Restriction Endonuclease Analysis as a Method To Determine porB Variable-Region Sequences in Nonserotypeable Meningococci - Dyet, Kristin H. (American Society for Microbiology, 2004)
porB PCR-amplicon restriction endonuclease analysis is a rapid, simple method developed to assess porB variation in nonserotypeable meningococci isolated during New Zealand's epidemic of meningococcal disease. Most nonserotypeable meningococci isolated between 1990 and 1999 inclusively either were type 4 (40.5%) or contained the porB variable region 1 (VR1)-19, VR2-D, VR3-7, and VR4-14a sequences (45.1%).